Evaluation of Rapid Impact Compaction method of sand for U-Tapao International Airport - Detcheewa, Sirasak; Youwai, Sompote; Sirisonthi, Athasit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Rapid Impact Compaction (RIC) is an alternative compaction technique which fills the gap of improving depth between shallow and deep compaction. The RIC technique is done by dropping the weight hammer on the circular base of the steel base on the ground. However, the effectiveness of the RIC method is based on compact soil. In this study, the effect of fine particle content in sandy soil on this compaction technique was studied. The field compaction test was carried out on the construction site of the apron at Utapao Airport at Ban chang, Rayong, Field trials use a total of three types of soil, with different fine content ranging from 18% to 33%. The compression effort is 25%, 50%, 75% and 100% of the standard energy of the proctor and the thickness filed by 3 and 5 m. Field test including Cone Penetration Test (CPT) and Plate load test (PLT) have been performed before and after the treatment to observe the efficiency of the RIC technique. Field test results show that low-fine soil is significantly improved. However, improvements are not clearly visible for soils with high fine content. The strength and stiffness of soil after improvement was significantly effects by the fine content of material. The effective depth of improvement by RIC is 4 m. from the ground surface.